(untitled) (REMUNOM, 2026)
This article presents the development of an innovative instrument for the assessment of political orientations, consisting of a multidimensional questionnaire with direct questions that were carefully designed to be sensitive and to minimize cognitive manipulation, aiming to reveal internal contradictions that are often concealed in traditional surveys. Grounded in theories from social psychology, political philosophy, and critical sociology, the instrument was implemented on an interactive digital platform built using the Django framework and responsive technologies, enabling scalable application and automated data analysis. The methodological combination seeks to address biases such as social desirability and cognitive dissonance, allowing for the observation of participants’ reflexive patterns in relation to their own beliefs. The results indicate potential for expanding the understanding of contemporary ideological complexities and fostering democratic debate, although further empirical validation is required to consolidate the tool’s effectiveness. The study contributes to the advancement of applied social sciences by offering technological and methodological resources for more accurate and reflective political research and interventions, as well as educational applications.